VALUE ADDED BUSINESS OF MILK FISH POND IN PINRANG REGENCY - Didi Rukmana; Rahmadani Rahmadani; Ariella Ramadhani Putri (Agribusiness Journal, 2021)
Milkfish is no longer just a superior commodity in Pinrang Regency, but it has become an inflation suppressor in South Sulawesi, so that representatives of Bank Indonesia South Sulawesi have made the milkfish commodity a development cluster in Pinrang Regency. This study aims to analyze the added value of various types of milkfish products processed by milkfish processing household industries in Pinrang Regency. The research was conducted in Pinrang Regency, South Sulawesi Province. The location selection was carried out purposively with the consideration that the location is an area where milkfish processing is located. The respondents used were one home industry. The data analysis used is descriptive qualitative method of data and information and Hayami method. The results showed the added value produced by the processing of boneless fish products with a small size of Rp. 3,450,-/head, medium size Rp. 6.182,-/head, large size Rp. 15,972,-/fish, shredded fish bone product Rp. 41,991,-/pack and Meatball products Rp. 60,923,-/ pack. This shows that the development of the milkfish processing industry provides added value (positive). It is hoped that the government can further develop the milkfish processing industry in Pinrang Regency because it can provide beneficial value for milkfish farmers.